Long noncoding RNA CA7-4 promotes autophagy and apoptosis via sponging MIR877-3P and MIR5680 in high glucose-induced vascular endothelial cells. Issue 1 (2nd January 2020) - Zhao, Xuan; Su, Le; He, Xiaoying; Zhao, Baoxiang; Miao, Junying
ABSTRACT: Vascular endothelial cells (VECs) that form the inner wall of blood vessels can be injured by high glucose-induced autophagy and apoptosis. Although the role of long noncoding RNA in regulating cell fate has received widespread attention, long noncoding RNAs (lncRNAs) that can both regulate autophagy and apoptosis need to be discovered. In this study, we identified that a small chemical molecule, 3-benzyl-5-([2-nitrophenoxy] methyl)-dihydrofuran-2(3H)-one (3BDO), synthesized by us, could inhibit VEC autophagy and apoptosis induced by a high concentration of glucose. To find new lncRNAs that regulate autophagy and apoptosis in VECs, we performed lncRNA microarray analysis. We found and verified an upregulated lncRNA named CA7-4 that was induced by a high concentration of glucose could be downregulated by 3BDO most obviously among all of the detected lncRNAs. Meanwhile, we investigated the mechanism of CA7-4 in regulating VEC autophagy and apoptosis. The results showed that CA7-4 facilitated endothelial autophagy and apoptosis as a competing endogenous RNA (ceRNA) by decoying MIR877-3P and MIR5680 . Further study elucidated that MIR877-3P could trigger the decrease of CTNNBIP1 (catenin beta interacting protein 1) by combining with its 3ʹ UTR and then upregulating CTNNB1 (catenin beta 1); MIR5680 inhibited the phosphorylation of AMP-activated protein kinase (AMPK) by targeting and decreasing DPP4 (dipeptidyl peptidase 4). Therefore, CA7-4, MIR877-3P and MIR5680 represent new signal pathways that regulate VEC autophagy and apoptosis under the high-glucose condition. Abbreviations : 3BDO: 3-benzyl-5-([2-nitrophenoxy] methyl)-dihydrofuran-2(3H)-one; 3ʹ UTR: 3ʹ untranslated region; AGO2: argonaute RISC catalytic component 2; AMPK: AMP-activated protein kinase/protein kinase AMP-activated; BAX/BCL2L4: BCL2 associated X, apoptosis regulator; BCL2: BCL2 apoptosis regulator; CASP3: caspase 3; ceRNA: competing endogenous RNA; CTNNB1: catenin beta 1; CTNNBIP1/ICAT: catenin beta interacting protein 1; DPP4: dipeptidyl peptidase 4; FGF2/FGF-2: fibroblast growth factor 2; HG: high concentration glucose (30 mM glucose); lncRNA: long noncoding RNA; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; miRNA: microRNA; MIR4778-3P : microRNA 4778-3p; MIR561-3P : microRNA 561-3p; MIR5680 : microRNA 5680; MIR877-3P : microRNA 877-3p; MTOR: mechanistic target of rapamycin kinase; Mut: mutant; NC: negative control; NG: normal concentration glucose (5.5 mM glucose); PARP1: poly(ADP-ribose) polymerase 1; qPCR: quantitative real-time PCR; RNA-FISH: RNA-ﬂuorescence in situ hybridization; ROS: reactive oxygen species; RT-PCR: reverse transcription polymerase chain reaction; siRNA: small interfering RNA; SQSTM1: sequestosome 1; TGFB2-OT1 : TGFB2 overlapping transcript 1; TUNEL: terminal deoxynucleotidyl transferase dUTP nick end labeling; VECs: vascular endothelial cells; WT: wild type